Implementation of an Improvement Cycle in the Compounding of Antineoplastic Therapy in a University Hospital - Luciana Moreira Dantas Barreto; Joyce Karolayne dos Santos Dantas; Tâmara Taynah Medeiros da Silva; Louise Constancia de Melo Alves Silva; Kauanny Vitoria Gurgel dos Santos; Laura Lima Souza; Daniele Vieira Dantas; Rodrigo Assis Neves Dantas (Health Care Science)
ABSTRACT Background Improving medication safety, particularly for high‐risk drugs, was identified as the third Global Patient Safety Challenge by the World Health Organization in 2017. Antineoplastic agents are included in the list of high‐risk medications because of their high potential to cause adverse events. This study evaluated the effectiveness of a project that was implemented to improve the antineoplastic therapy compounding process at a university hospital. Methods This study had a quasi‐experimental before‐and‐after design and used a quantitative approach to investigate the effects of implementation of this project in a centralized intravenous admixture service. The compounding of antineoplastic therapy was evaluated using five quality criteria at three time points: an initial evaluation and two post‐intervention re‐evaluations. The results of the intervention were subjected to statistical analysis and are presented in a Pareto chart. Results All five quality criteria for correct compounding of antineoplastic therapy improved after implementation of the intervention, with an increase in compliance values for all criteria after the second evaluation. Improvements in criteria 1, 3, and 4 were statistically significant. Conclusions The implementation of the improvement project enhanced the quality criteria and caused a cultural shift in the team, with an improved view towards quality management in work processes.